The Effects of U.S. Trade Protection and Promotion Policies. - Feenstra, Robert C. (National Bureau of Economic Research project report., 1997)
Economists disagree on whether recent U.S. trade policies are harmful or helpful, but they all agree that there is a new trend toward focusing on results-oriented policies in specific markets and with particular trading partners. These twelve essays by leading international economists explore crucial issues in U.S. trade policy today. Topics examined include the markets for automobile and automobile parts in the United States and Japan, the U.S. response to "unfair" trading practices such as dumping, and the effects of industry- and country-specific policies. Examples include high-te.